Strategi Guru dalam Mengembangkan Kreativitas Anak Usia 4-5 Tahun melalui Kegiatan Seni Rupa di KB Bhakti Pertiwi Kecamatan Kampar Kiri Hilir - Cici Cici; Susi Herlinda; Herwina Herwina (Asian Journal of Early Childhood and Elementary Education, 2026)
The creativity development of children aged 4–5 years in visual arts activities at KB Bhakti Pertiwi, Kampar Kiri Hilir Subdistrict, has not developed optimally, as indicated by the children’s continuing difficulties in expressing ideas and imagination through drawing, coloring, and pasting activities. This study aims to describe teachers’ strategies in developing children’s creativity through visual arts activities. This study employed a qualitative approach with a descriptive method. The research subjects consisted of 13 children aged 4–5 years, with two main informants, namely the principal and the classroom teacher. Data were collected through observation, interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that teachers’ strategies in developing children’s creativity were implemented through three main stages, namely planning, implementation, and evaluation. At the planning stage, the teacher prepared the RPPH, media, and interesting visual arts materials that were appropriate to the children’s characteristics. At the implementation stage, the teacher gave children the freedom to express themselves through drawing, coloring, and collage activities without pressure, accompanied by motivation and positive support. At the evaluation stage, the teacher assessed the process and the children’s work results and provided appreciation for every effort made. The research findings showed that most children were in the categories of Developing as Expected and Developing Very Well. Thus, learning strategies that provide freedom of expression, emotional support, and the use of varied art media contribute to the optimal development of early childhood creativity.